Emergency Department staff experiences of screening and response for intimate partner violence in a multi-site feasibility study: Acceptability, enablers and barriers. (September 2022) - Spangaro, Jo; Vajda, Jacqualine; Klineberg, Emily; Lin, Sen; Griffiths, Christine; McNamara, Lorna; Saberi, Elham; Field, Emma; Miller, Alex
Abstract: Background: Intimate partner violence is a lead cause of ill health and premature death among Australian women. Abused women are likely to present to Emergency Departments. Routine screening provides opportunities to identify and respond to intimate partner violence. Methods: A six-month screening feasibility study was conducted in two rural and one urban NSW Emergency Departments. Surveys with participating nurses, medical officers and social workers, as well as focus groups with nurses and social workers were conducted at each site to understand their experience. Results: Survey respondents (n = 198) agreed it was appropriate (87%) and acceptable (91%) to screen for intimate partner violence in Emergency Departments. Overall 62% of respondents suggested screening had positive impacts on womens' care. Focus group discussions with 39 nurses and social workers identified enablers of screening as: ease of use of the screening tool; availability of social work response within one hour (as per the study protocol); and executive support. Barriers were: high patient volume; lack of integration with existing processes; lack of privacy and brevity of training. Conclusions: Screening in Emergency Departments was strongly supported by health practitioners who responded to the survey. Work is needed to address competing demands, integration of screening processes, and staff training.